Systems integration to promote the mental health of Aboriginal and Torres Strait Islander children: protocol for a community-driven continuous quality improvement approach - Janya McCalman; Roxanne Bainbridge; Yvonne Cadet James; Ross Bailie; Komla Tsey; Veronica Matthews; Michael Ungar; Deborah Askew; Ruth Fagan; Hannah Visser; Geoffrey Spurling; Nikki Percival; et al. (BMC Public Health, 2020)
Abstract Background Systems integration to promote the mental health of Aboriginal and Torres Strait Islander children works towards developing a spectrum of effective, community-based services and supports. These services and supports are organised into a coordinated network, build meaningful partnerships with families and address their cultural and linguistic needs, to help children to function better at home, in school, in the community, and throughout life. This study is conducted in partnership with primary healthcare (PHC) and other services in three diverse Indigenous Australian communities. It entails conceptualising, co-designing, implementing, and evaluating the effectiveness of systems integration to promote the mental health and wellbeing of Indigenous school-aged children (4–17 years). This paper outlines a protocol for implementing such complex community-driven research. Methods/design Using continuous quality improvement processes, community co-designed strategies for improved systems integration will be informed by narratives from yarning circles with Indigenous children and service providers, and quantitative data from surveys of service providers and audits of PHC client records and intersectoral systems. Agreed strategies to improve the integration of community-based services and supports will be modelled using microsimulation software, with a preferred model implemented in each community. The evaluation will investigate changes in the: 1) availability of services that are community-driven, youth-informed and culturally competent; 2) extent of collaborative service networks; 3) identification by PHC services of children’s social and emotional wellbeing concerns; and 4) ratio of children receiving services to identified need. Costs and benefits of improvements to systems integration will also be calculated. Discussion The study will provide evidence-informed, community-driven, and tested models that can be used for implementing systems integration to promote the mental health and wellbeing of Indigenous children. It will identify the situational enablers and barriers that impact systems integration and determine the extent to which systems integration improves service availability, systems and child outcomes. Evidence for the cost effectiveness of systems-level integration will contribute to national mental health policy reform.